PEMETAAN POTENSI ENERGI GELOMBANG LAUT DI PERAIRAN INDONESIA MENGGUNAKAN METODE PEMODELAN NUMERIK SWAN - Mu'aqil Uham, Muhammad
The demand for electricity in Indonesia increased by approximately 4.6% annually. This study aims to map the potential of wave energy, using a wave spectral numerical modeling method, which can be used to identify differences in characteristics of waves in Indonesian waters. To build such a numerical model, bathymetric and wind data in the area of research are required as input to the SWAN (Simulating Waves Nearshore) for calculating wave in several different conditions. The size of wave in its growing regions depends on wind speed, duration or length the wind blows, and wave travelling time since its early growth (fetch). Indonesia, which is crossed by the equator, significantly affects the length of fetch. In addition, the presence of islands along Indonesian waters also affect the fetch formed. Potential mapping is done by taking 10 point samples to quantify the value of the power generated, which is amounted about 49,705.730 W or 435,422,193.100 kWh (8760 hours) a year. Potential mapping also done by quantifying the overall value in the mapping area. Indonesian waters at least have theoretical potential power of ocean waves about 709,721,526.509 W. Then, classification of area that could potentially have large wave energy is done by dividing the power value into five classes (very potential, potential, quite potential, less potential, and no potential). Areas with the highest potential are in the area of the Strait of Karimata directly adjacent to the South China Sea (the Natuna waters), the south coast of Java, Bali, Lombok, Flores that directly adjacent to the Indian Ocean, the west coast of Sumatra, and Arafuru Sea waters.